5x^2+ 8x -69=0 solve by factoring

5x^2 + 8x - 69 = (5x+23)(x-3) = 0

x = -23/5, 3

Ideas: 5*(-69) = 23*(-15), and 23-15 = 8, the coefficient of x.

So, 5x^2 + 8x -69 = 5x^2-15x + 23x-69 = 5x(x-3) + 23(x-3) = (5x+23)(x-3)

5x^2+ 8x -69=0 solve by factoring

Tutors, sign in to answer this question.

5x^2 + 8x - 69 = (5x+23)(x-3) = 0

x = -23/5, 3

Ideas: 5*(-69) = 23*(-15), and 23-15 = 8, the coefficient of x.

So, 5x^2 + 8x -69 = 5x^2-15x + 23x-69 = 5x(x-3) + 23(x-3) = (5x+23)(x-3)

Parviz F. | Mathematics professor at Community CollegesMathematics professor at Community Colle...

5X^2 + 8X -69 =0

Have to find out 2 numbers whose Sum is 8 and product is 5* 69 =- 345

first write 345 as product of its prime factor, by doing division 3

345 = 3 * 5 * 23 , find 2 factors whose difference is - 8, 15&23.

Break 8x into 2 parts 23, 15

5 X^{2} - 15X + 23X - 69 =0

Now we factor by Grouping

5X( X -3) +23( X -3 ) = ( X - 3 ) ( 5X + 23)

(5x + 23)(x - 3)

Hi Rachel. I will solve a similar problem, via a method called group factoring. Then, I will show how this relates to solving your problem. Note first that this equation has the form, a*x^2 + b*x + c = 0. For example, 3x^2 - 17x - 56 = 0.

Solution Steps.

Step 1: multiply a by c. Here, we have that 3*( -56) = -168.

Step 2: Find two factors of the product in step 1 that will multiply to give that same product and add to give b, that is, -17 in his example (see the original example above). Note that -24*7 = -168, and -24 + 7 = -17, as desired.

Step 3: Note that the factors in step 2 pertain to the coefficient of x in the originalequation. So now, rewrite bx as a sum, using the factors that we just got in step 2. Here, we rewrite -17x as -24x +7x. Now, rewrite the whole equasuit using this new replacement. We get the equation 3x^2 -24x +7x -56 = 0.

Step 4: factor the last equation, from step 3 by splitting it into two groups and factoring each group completely as follows, on the left side of the equation. We do this as follows:

3x^2 - 24x + 7x - 56 = 0 becomes

3x(x-8)+7(x-8)=0, where we note that (x-8) is common to both the left sum and the right summand, and so we can factor out the (x -8) to get the equation

(x-8)(3x+7)=0 which tells uat that x -8 =0, whence x=8, and/or 3x+7=0 whence 3x =-7 whence x = -7/3.

I will now start you out with your problem which you can use my the above steps to complete...

Step1: Multiply 5 by -69 to get -345.

Step 2: Here we see that the useful factors of -345 are -23 and 15, since -23 *15 = -345, and -23 + 15 = 8, as required.

Now, you can finish the problem, using the steps in my guided example.

All the best!

Already have an account? Log in

By signing up, I agree to Wyzant’s terms of use and privacy policy.

Or

To present the tutors that are the best fit for you, we’ll need your ZIP code.

Your Facebook email address is associated with a Wyzant tutor account. Please use a different email address to create a new student account.

Good news! It looks like you already have an account registered with the email address **you provided**.

It looks like this is your first time here. Welcome!

To present the tutors that are the best fit for you, we’ll need your ZIP code.

Please try again, our system had a problem processing your request.

## Comments

I accidentally voted down my contribution, complements of my ancient iPad.